2011
DOI: 10.1369/0022155411428468
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Expression of γ-Glutamyl Cyclotransferase Suggests It Is Not a General Tumor Marker

Abstract: Summary γ-Glutamyl cyclotransferase (GGCT) contributes to the γ-glutamyl cycle that regulates glutathione metabolism. Although GGCT has been implicated in several studies as a possible cancer marker, little is known about its distribution in cells and tissues. The authors investigated GGCT expression in normal tissues and tumors using Western blots and immunohistochemistry with a novel anti-GGCT monoclonal antibody. GGCT was detected in most organs and was mainly found in epithelial cells. Although the intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The GSH metabolism pathway contributes to the detoxification and elimination of a wide range of xenobiotic compounds, underscoring the role of redox regulation of MDR mediated by drug efflux pumps 32 33 34 . In several previous studies GGCT, a critical component of the GSH pathway, has been implicated as a cancer marker with a potential role in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GSH metabolism pathway contributes to the detoxification and elimination of a wide range of xenobiotic compounds, underscoring the role of redox regulation of MDR mediated by drug efflux pumps 32 33 34 . In several previous studies GGCT, a critical component of the GSH pathway, has been implicated as a cancer marker with a potential role in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The γ-glutamyl cycle is a pathway that encompasses the synthesis and degradation of GSH and is thought to contribute to the uptake of amino acids across cellular membranes 38 . GGCT is a pivotal enzyme that contributes to the γ-glutamyl cycle regulating GSH metabolism through catalyzing the formation of 5-oxoproline (pyroglutamic acid) from γ-glutamyl dipeptides 34 39 . Aaron J Oakley et al reported 39 that the inhibition of GGCT in cases of GSH synthetase deficiency blocks the degradation of γ-glutamylcysteine and allows it to accumulate to a level where it may partially substitute for GSH in redox and detoxification reactions ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They examined more than 30 normal organ samples and reported weak to moderate immunoreactivity in a wide range of normal tissues. Amano et al also studied the immunohistochemical expression of GGCT in many normal tissues [ 13 ]. They also reported that GGCT protein was detected in most normal human tissues and mainly in epithelial cells.…”
Section: Distribution and Intracellular Localization Of Ggct In Nomentioning
confidence: 99%
“…They found that the region consisting of 61–120 amino acids is required for the full-length GGCT to anchor in the cytoplasm and they elucidated that deletion of this region allows GGCT to move to the nucleus. Although the role of GGCT in the nucleus has not been determined, the GGCT observed in the nucleus may represent a posttranslationally modified form or a splice variant [ 13 ].…”
Section: Distribution and Intracellular Localization Of Ggct In Nomentioning
confidence: 99%
See 1 more Smart Citation